Screening for refractive errors in 6-9 month old infants by photorefraction. Issue 2 (February 1984) - Atkinson, J.; Braddick, O. J.; Durden, K.; Watson, P. G.; Atkinson, S.
Abstract : The method of isotropic photorefraction has been used in a trial of refractive screening of 6-9 month old infants. Data are presented on the calibration of the method against retinoscopic measurements and its reliability. In photorefractive screening of 1096 infants under cyclopentolate cycloplegia 5% were found to be hypermetropic (over +3.5 D), 4.5% myopic, and 1.3% anisometropic (over 1 D). These refractive errors were confirmed on retinoscopic follow-up (with the exception of a few anisometropes). Follow-up of controls shows that one small refractive error was missed in 52 infants. We conclude that photorefraction is a valid and practical screening technique. Longitudinal study of infants with refractive errors will assess the value of early detection, in particular for prediction and prevention of strabismus.